Bacterial adhesion to collagens: implications for biofilm formation and disease progression in the oral cavity. (2nd January 2022) - Álvarez, Simón; Leiva-Sabadini, Camila; Schuh, Christina M. A. P.; Aguayo, Sebastian
Abstract: Collagen is the most abundant structural protein in the body and the main component of the extracellular matrix of most tissues, including dentine and periodontal tissues. Despite the well-characterized role of collagen and specifically type-I collagen, as a ligand for host cells, its role as a substrate for bacterial adhesion and biofilm formation is less explored. Therefore, the purpose of this review is to discuss recent findings regarding the adhesion of oral bacteria to collagen surfaces and its role in the progression and severity of oral and systemic diseases. Initial oral colonizers such as streptococci have evolved collagen-binding proteins (cbp) that are important for the colonization of dentine and periodontal tissues. Also, periodontal pathogens such as Porphyromonas gingivalis and Tannerella forsythia utilise cbps for tissue sensing and subsequent invasion. The implications of bacteria-collagen coupling in the context of collagen biomaterials and regenerative dentistry approaches are also addressed. Furthermore, the importance of interdisciplinary techniques such as atomic force microscopy for the nanocharacterization of bacteria-collagen interactions is also considered. Overall, understanding the process of oral bacterial adhesion onto collagen is important for developing future therapeutic approaches against oral and systemic diseases, by modulating the early stages of biofilm formation.